Geographical distribution of cystic fibrosis carriers as population genetic determinant of COVID-19 spread and fatality in 37 countries - Gabbi, Chiara; Renieri, Alessandra; Strandvik, Birgitta (The Journal of infection, 2022)
•Ecological study in 37 countries during the first pandemic wave.•Prevalence of cystic fibrosis used as indicator of the geographical distribution of CF carriers.•COVID-19 prevalence directly correlates with country CF prevalence.•COVID-19 Case Fatality Rate directly correlates with country CF prevalence.•Population genetics of CFTR associates with the spatial distribution of COVID-19 spread and fatality. COVID-19 has shown a relevant heterogeneity in spread and fatality among countries together with a significant variability in its clinical presentation, indicating that host genetic factors may influence COVID-19 pathogenicity. Indeed, subjects carrying single pathogenic variants of the Cystic Fibrosis (CF) Transmembrane Conductance Regulator (CFTR) gene – i.e. CF carriers – are more susceptible to respiratory tract infections and are more likely to undergo severe COVID-19 with higher risk of 14-day mortality. Given that CF carrier prevalence varies among ethnicities and nations, an ecological study in 37 countries was conducted, in order to determine to what extent the diverse CF carrier geographical distribution may have affected COVID-19 spread and fatality during the first pandemic wave. The CF prevalence in countries, as indicator of the geographical distribution of CF carriers, significantly correlated in a direct manner with both COVID-19 prevalence and its Case Fatality Rate (CFR). In a regression study weighted for the number of tests performed, COVID-19 prevalence positively correlated with CF prevalence, while CFR correlated with population percentage older than 65-year, cancer and CF prevalence. Multivariate regression model also confirmed COVID-19 CFR to be associated with CF prevalence, after adjusting for elderly, cancer prevalence, and weighting for the number of tests performed. This study suggests a putative contribution of population genetics of CFTR in understanding the spatial distribution of COVID-19 spread and fatality.